Religiusitas Holistik dalam Kebijakan Kementerian Agama terhadap Orientasi Majelis Taklim di Indonesia - Istiani, Nurul (POROS ONIM: Jurnal Sosial Keagamaan, 2023)
Social and religious problems in the midst of globalization are a major challenge for the life of modern society, including Indonesian muslims. The purpose of this study is to identify and explore the values of religiosity in the orientation of the taklim assembly in the Regulation of the Minister of Religious Affairs no.29 of 2019 concerning the Majelis Taklim. Qualitative studies in the form of literature studies use a normative-philosophical approach. The theory of the dimension of religiosity formulated by C.Y. Glock and R. Stark became the theory of analysis of the focus of study discussion. Research data is obtained through documentation techniques. Meanwhile, data analysis techniques through data reduction, presentation, and verification.This study concludes that there is a dimension of increasing various aspects of religiosity in the political policy of the Ministry of Religious Affairs related to the orientation of majelis taklim in Indonesia, including the increasing of religious social attitudes in the formation of pluralist, humanist, and nationalist personalities, and the improvement of intellectual, faith, ritual, and spiritual in the formation of scientific and religious personalities. The theoretical implications of this study show that increasing religious religiosity holistically can be internalized through the political policies of non-formal religious educational institutions in Indonesia. The limitations of this study have not examined practical problems related to the orientation of increasing the variety of dimensions of religiosity in the activities of majelis taklim in Indonesia.